Respuesta :

it's just y= cos(x)+6

Answer:

[tex]y=cos(x)+6[/tex].

Step-by-step explanation:

We are asked to write an equation for the translation of the function [tex]y=cos(x)[/tex] to 6 units upwards.

Let us recall transformation rules.

[tex]f(x)\rightarrow f(x+a)=\text{Graph shifted to left by a units}[/tex]

[tex]f(x)\rightarrow f(x-a)=\text{Graph shifted to right by a units}[/tex]

[tex]f(x)\rightarrow f(x)+a=\text{Graph shifted upwards by a units}[/tex]

[tex]f(x)\rightarrow f(x)-a=\text{Graph shifted downwards by a units}[/tex]

Since we need to shift our given function 6 units upwards, so we will add 6 to our given function outside the parenthesis as:

[tex]y=cos(x)+6[/tex]

Therefore, our required equation would be [tex]y=cos(x)+6[/tex].